(untitled) (Journal of the College of Education for Women, 2018)
The current study was concerned to address these gaps in literature by identifying: first level and type of future visions among the next graduation student, second level and type of future visions among the sample according to gender (Male- Female), third level of the illegal immigration among the sample, fourth level of the illegal immigration according to gender (Male, Female), and finally the relationship between future visions and illegal immigration. To achieve the aims of the current study, the researchers created a questionnaire for the future visions. The psychometric properties (e.g. face validity, structure validity, and reliability) were tested. Base on the current sample, results showed that the questionnaire had sound psychometric properties. In terms of the illegal immigration, a questionnaire created by Nusairah 2011 was adopted. Two hundred students were recruited. To analyze the data, t-test for one sample, t-test for two samples, Pearson Correlation Coefficient, and Spearman formula were used. The results of the current study showed that there is: A high level of negative future visions among the sample. No significant differences in future visions between male and female, whereas there is on difference according to specializations. A high level of illegal immigration attitude was found among the sample. Results also showed that there are significant differences in illegal immigration attitudes between male and female, whereas there is no difference according to specializations. The results suugusted that there is a strong relationship between future visions and and illegal immigration attitude.